Дослідження європейського досвіду в подоланні проблем забезпечення населення України житлом - Баланська, О. І.; Панченко, А. В.; Мельник, В. М.; Balanska, O.; Panchenko, A.; Melnyk, V. (Видавництво Львівської політехніки, 2018)
Проаналізовано ситуацію, що склалася на ринку житла в Україні, зокрема рівень забезпеченості ним населення. Виділено основні проблеми, що існують у цьому секторі економіки, зокрема низький рівень купівельної спроможності населення країни. Досліджено стан житлового забезпечення у країнах Європи та визначено основні відмінності між ними та Україною. Запропоновано заходи, які ґрунтуються на вико- ристанні досвіду розвинених країн у забезпеченні населення житлом, для використання в Україні, зокрема розширення іпотечного кредитування та впровадження інституту соціального житла.

Despite the recent increase of the size of the minimum and average wages and due to high inflation, the purchasing power of the population has not increased. There is the stable low level of housing in Ukraine and a significant number of people in queues for housing or housing improvement, have all the chances not get the desired at all according to the pace of housing. Also, in the country, even housing that is considered habitable is often even not close to the norms of European countries. Although the volume of housing construction in Ukraine is increasing every year, there is a significant number of people in the country who are not members of the socially vulnerable population or are not below the poverty line, but they can not afford themselves to buy housing. That is why there is a need to search for such ways of providing the population with housing, which made it possible to solve the problem on a personal basis, instead of transferring it to the state. To accomplish these tasks it is expedient to study the European experience in providing the population with housing and find ways to use it in domestic conditions. One of the main differences between Ukraine and Europe is that we have no social housing institute that would be in state ownership and provided to low-income groups of the population for a low rent for a certain time before improving their financial status. It is also typical for Europeans that most of the population does not own a home, but permanently resides in rented accommodation. Mortgage loans are the main source of financing for housing construction in developed countries, in Ukraine they account for a very small share in total. This is particularly due to very high lending rates, as well as the instability of the country's economic system and, consequently, the lack of confidence in the future of the majority of the population. The calculations made in article show that in Ukraine, at the lowest wage, housing prices are quite equal to European ones. At the same time, we have the highest mortgage rates and, accordingly, payouts on issued loans. Thus, for the majority of the Ukrainian population to buy housing on their own is an overriding task, and even lower mortgage rates can not drastically change the situation and therefore there is a need to find other ways to solve the housing supply problem. The article substantiates that for the gradual solution of the problem of housing provision in Ukraine, first of all, it should be developed by the institution of social housing, which would allow to at least partially reduce the number of people in queues. As soon as possibility to receive free housing in property does not stimulate people for improving their living conditions themselves. And if people know that they will be provided with housing temporarily and only on lease rights, then some of them will be removed from the queues. Reducing interest rates on mortgages, along with the introduction of social housing will encourage people to buy their own housing.
Research of the european experience in overcoming problems of providing Ukraine's population housing
Keywords: житло; іпотечне кредитування; забезпеченість житлом; середня заробітна плата; житловий фонд; фінансування житлового будівництва; housing; mortgage lending; housing provision; average wages; housing fund; housing financing; 365.26